Novel Effector RHIFs Identified From Acidovorax avenae Strains N1141 and K1 Play Different Roles in Host and Non-host Plants - Nakamura, Minami; Kondo, Machiko; Suzuki, Aika; Hirai, Hiroyuki; Che, Fang-Sik (Frontiers in Plant Science, 2021)
Plant pathogenic bacteria inject effectors into plant cells using type III secretion systems (T3SS) to evade plant immune systems and facilitate infection. In contrast, plants have evolved defense systems called effector-triggered immunity (ETI) that can detect such effectors during co-evolution with pathogens. The rice-avirulent strain N1141 of the bacterial pathogen Acidovorax avenae causes rice ETI, including hypersensitive response (HR) cell death in a T3SS-dependent manner, suggesting that strain N1141 expresses an ETI-inducing effector. By screening 6,200 transposon-tagged N1141 mutants based on their ability to induce HR cell death, we identified 17 mutants lacking this ability. Sequence analysis and T3SS-mediated intracellular transport showed that a protein called rice HR cell death inducing-factor (RHIF) is a candidate effector protein that causes HR cell death in rice. RHIF-disrupted N1141 lacks the ability to induce HR cell death, whereas RHIF expression in this mutant complemented this ability. In contrast, RHIF from rice-virulent strain K1 functions as an ETI inducer in the non-host plant finger millet. Furthermore, the infectivity of RHIF-deficient N1141 or RHIF-deficient K1 strains to the corresponding host plants was reduced. Collectively, novel effector RHIFs identified from A. avenae strains N1141 and K1 function in establishing infection in host plants and in ETI induction in non-host plants.